Analisis Faktor Penyebab Keterlambatan Sekolah Siswa Kelas III SDK Kalembu Ligha dan Dampaknya Terhadap Hasil Belajar - Ghogha, Heronima; Lede, Yulius Keremata; Making, Samuel Rex M. (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims to determine the factors that cause for school delaays for class III students at SDK Kalembu Ligha and their impact on learning outcomes. This type of research is qualitative research using deskriptive methods carried out in from of observation, interviews, dokumentation and data analisys techniques including, data reduction, data presentation and drawing conclusions and verification. This research was carried out in class III of SDK Kalembu Ligha with a total of 12 students. The results of the research show that the faktors that cause class III student to be late for school are internal faktors and eksternal faktors. Internal faktor include student often waking up late, and eksternal faktors, namely, student are still busy on the road. The distance traveled from home to school is very far, about 2.